Challenges Encountered in the Implementation of Online Distance Learning - Clarin, Analyn S.; Baluyos, Esther L. (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Teachers face several drawbacks and potential issues while participating in an online class. This study explored the challenges encountered by teachers in implementing online distance learning in the Basic Education Department, specifically in the Junior and Senior High School, of Misamis University, Ozamiz City. The study utilized a qualitative approach using phenomenological design. The study included twenty (20) participants from the teachers handling online classes in the Junior and Senior High Schools, selected through purposive sampling. In-depth face-to-face interviews were used in gathering information from the teachers. The researcher employed the seven steps of Colaizzi’s method of data analysis. Results revealed the following themes: (1) the need to motivate the students in learning the lessons; (2) the preparation of learning resources; (3) poor internet connection; and (4) constant communication with students and parents. Teachers may integrate activities that would keep the students engaged throughout the lesson. Back-up plans may be designed to address the challenge of internet connectivity which interfere the teaching-learning process.